2017
DOI: 10.1002/ase.1690
|View full text |Cite
|
Sign up to set email alerts
|

“Applying anatomy to something I care about”: Authentic inquiry learning and student experiences of an inquiry project

Abstract: Despite advances to move anatomy education away from its didactic history, there is a continued need for students to contextualize their studies to make learning more meaningful. This article investigates authentic learning in the context of an inquiry-based approach to learning human gross anatomy. Utilizing a case-study design with three groups of students (n = 18) and their facilitators (n = 3), methods of classroom observations, interviews, and artifact collection were utilized to investigate students' exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…It is conducted every week from three hours of laboratory sessions per two weeks to two hours of laboratory sessions per week. It increased the time students spent in the laboratory from 18 to 24 hours (Smallhorn et al 2015), research conducted for 1 hour in the experimental class and 1 hour in traditional classes (Nybo and May 2015), while other research did not explain the duration and the period of the research conducted (Yildirim et al 2014;Yewang 2017;Anstey 2017;Wang et al 2014;Biru et al 2018).…”
Section: Duration and Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conducted every week from three hours of laboratory sessions per two weeks to two hours of laboratory sessions per week. It increased the time students spent in the laboratory from 18 to 24 hours (Smallhorn et al 2015), research conducted for 1 hour in the experimental class and 1 hour in traditional classes (Nybo and May 2015), while other research did not explain the duration and the period of the research conducted (Yildirim et al 2014;Yewang 2017;Anstey 2017;Wang et al 2014;Biru et al 2018).…”
Section: Duration and Periodmentioning
confidence: 99%
“…There are 13 articles that have been reviewed; two articles discussed Mobile inquiry-based learning (M-IBL). Mobile inquiry learning is inquiry learning supported by the use of mobile devices (Chang et al 2016;Cheng et al 2016), One article discusses an online inquiry learning that is learned using the web-based inquiry method (Hsu 2014), six articles discussed about inquirybased learning (Yildirim et al 2014;Smallhorn et al 2015;Anstey 2017;Biru et al 2018;Wang et al 2014;Nybo and May 2015), Three articles discussed about the guided inquiry and free inquiry (Yewang 2017;Yunistika and Juanengsih 2018;Ural 2016).…”
Section: Type Of Inquiry Learningmentioning
confidence: 99%
“…Inquiry‐based learning involves active and independent investigation of questions and problems that are of interest to students through the process of scientific inquiry (Lee et al, ). Inquiry‐based learning has been shown to provide many benefits to students (Bonstetter, ; Brown et al, ; Lee, ; Levy, ; Anstey et al, , ). Generally, this learning approach has been shown to develop critical thinking skills (Holaday and Buckley, ) and independent problem‐solving skills (Madil et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, this learning approach has been shown to develop critical thinking skills (Holaday and Buckley, ) and independent problem‐solving skills (Madil et al, ). Anstey () reported that inquiry learning in anatomy, where students pursue their own interests, provided an unique learning experience for students driven by their own curiosities. Furthermore, studies of IBL in anatomy classrooms have shown gains in self‐perceived research abilities (Bentley et al, ) and an improved understanding of content learned (Chaplin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Later on, these students will reproduce those contents, the anatomical details studied, to their peers [8]. In this sense, students can engage anatomical understandings to their personal abilities [1]. These activities were also perceived to enhance motivation and improve understanding of the subject to students, both Table Leaders and passive peers [14].…”
Section: Introductionmentioning
confidence: 99%